The Influence of Pedagogical Competence and Self-Efficacy on Teacher Performance Moderated by Academic Supervision - Handayani Handayani; Sunarto Sunarto; Ilham Susilo Bakti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to analyze the effect of educational competence and self-efficacy on teacher performance moderated by academic supervision of vocational school teachers in Bumijawa District, Tegal Regency. This type of research is explanatory research with a quantitative approach. The population in this study were SMK teachers in Bumijawa District, Tegal Regency, with a total population of 113 people. All members of the people as respondents. Of the 113 questionnaires distributed, 108 were returned. Based on the F test, it was found that the model deserves to be analyzed further. The coefficient of determination test results describes the independent variable X1 to the dependent variable and X2 to the dependent variable. The hypothesis was tested using a t-test using Moderation Regression Analysis (MRA). The results showed that educational competence affected teacher performance, self-efficacy did not affect teacher performance, academic supervision affected teacher performance, visionary leadership moderated the effect of educational competence on teacher performance, and academic management did not moderate the impact of self-efficacy on teacher performance.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//